(untitled) (World Economics and Finance Bulletin, 2023)
In this article, based on the analysis of the main indicators of agricultural production, the current state of development of the agricultural sector is revealed. Information about the adoption of the strategy for the development of agriculture of the Republic of Uzbekistan for 2020-2030 is provided, the main tasks of strategic priorities and the results achieved on them are highlighted